TYPE 2 DIABETES IN CHILDREN AND ADOLESCENT: FROM PATHOGENESIS TO TREATMENT - A.B. Resnenko (Union of pediatricians of Russia, 2011)
Dramatic rising prevalence of type 2 diabetes among children and adolescent required from health care providers to develop a new strategies for screening, treatment and prevention of diabetes at this age. Many medications have been developed for treatment of type 2 diabetes in adult. Despite on this, therapeutic modalities in children and adolescent remain extremely limited. This review discussed modern data about pathogenesis diabetes type 2 and main risk-factors. Author presents an update on management of type 2 diabetes in young patients.Key words: diabetes type 2, prevalence, causes treatment, metformin, children.